Prenatal Exposure to Ambient Fine Particulate Matter (PM₂.₅) and Adverse Perinatal Outcomes: A Literature Review - Korolchuk, Anhelina; Palacz, Bartosz; Teper, Maria Magdalena; Kubiś, Natalia Marianna; Wrona, Julia Anna; Perz, Wiktor; Polus, Aleksander; Piotrowski, Jędrzej; Gluzicka, Anna; Olczyk, Liwia (Journal of Education, Health and Sport, 2026)
Background. Prenatal exposure to fine particulate matter (PM₂.₅), composed of airborne particles smaller than 2.5 micrometers, is a significant environmental risk that can adversely affect pregnancy. Exposure to PM₂.₅ during pregnancy has been associated with a number of adverse birth outcomes, including small for gestational age (SGA), low birth weight (LBW), and preterm birth (PTB). This literature review summarizes evidence published between 2020 and 2025 regarding the relationship between prenatal PM₂.₅ exposure during different pregnancy trimesters and the risk of PTB, LBW, and SGA. Aim of the review. This review gathers and evaluates epidemiological studies from 2020 to 2025 examining the connection between prenatal exposure to PM₂.₅ and adverse perinatal outcomes such as SGA, LBW, and PTB Methods. In our review, we included case-control and cohort primary epidemiological studies that were published between 2020 and 2025. Maternal exposure to ambient PM₂.₅ in connection with PTB, LBW, or SGA was evaluated in eligible studies. Results. Across the reviewed studies, prenatal exposure to PM₂.₅ was linked to an increased risk of LBW and SGA, with heightened susceptibility in the first and second trimesters. Associations with PTB were also noted but more variable. Many large population-based studies found small but statistically significant effects, especially those using thorough exposure assessment methods. Conclusions. The current evidence suggests that maternal exposure to ambient PM₂.₅ during pregnancy is associated with an increased risk of adverse birth outcomes, especially indicators of restricted fetal growth. These findings highlight the need for further study to clarify critical exposure windows, underlying biological processes, and effective strategies to reduce exposure during pregnancy. They also support the importance of air quality as a controllable environmental factor for maternal and offspring health.